1990
DOI: 10.1007/pl00020015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeine intake during gestation and lactation on bones of young growing rats

Abstract: The objective of this study was to evaluate the extended effect of caffeine intake received during gestation and lactation on the mandible and femur of rats. Timed-pregnant dams were divided into two groups. Dams of group 1 were fed a 20% protein diet throughout the experimental period from day 9 of gestation. Dams of group 2 were also fed a 20% protein diet, supplemented with caffeine (lmg/100 g of body weight). Upon delivery, 8 pups were assigned to each dam, and the dams were continued on their respective d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Also experimental studies did not provide conclusive results on the effects of coffee/caffeine on the skeletal system. Although deleterious effects of caffeine have been reported in rats [14][15][16][17][18][19][20][21][22][23][24], it has been observed that long-term administration of coffee in the diet did not damage the rat skeletal system [25].…”
Section: Introductionmentioning
confidence: 99%
“…Also experimental studies did not provide conclusive results on the effects of coffee/caffeine on the skeletal system. Although deleterious effects of caffeine have been reported in rats [14][15][16][17][18][19][20][21][22][23][24], it has been observed that long-term administration of coffee in the diet did not damage the rat skeletal system [25].…”
Section: Introductionmentioning
confidence: 99%
“…29 Density can be calculated by using the relation given below; Entire femur has been dehydrated with ethanol.…”
Section: Preclinical Experimentsmentioning
confidence: 99%
“…Density of the solid (bone) can be determined by volume displacement because submerged object displaces a volume equal to its own volume. 29 Density can be calculated by using the relation given below;…”
Section: Dry Bone Weight Bone Volume and Bone Density Measurementsmentioning
confidence: 99%
“…In a study examining the effect of maternal caffeine intake on fetal bone, Nakamato et al (1999) found that, normal growth and development of the fetal bone are impaired as a result of maternal caffeine intake (Nakamoto, Grant & Yazdani, 1999). The early effects of caffeine in the maternal diet were lasting as noted by the lack of recovery of the offspring even after changing to a caffeine-free diet (Schneider, Miller & Nakamoto, 1990). These results may grant some backing to our study giving that caffeine in the form of coffee, tea and cola are among the most consumable drinks in the world, and most of the study population was fed either expressed breast milk or donor breast milk.…”
Section: Is Caffiene a Risk For Op? 49mentioning
confidence: 99%